A civil action - Harr, Jonathan (New York Random House, 1995)
"The lawyer had not wanted the case at first--it was too big, too complicated, too risky. Two of the nation's largest corporations stood accused of the deaths of children in a small town north of Boston. Against his better judgment, the lawyer found himself drawn into the case." "In this book, you'll meet the Harvard law professor who told the lawyer that this case was worth a billion dollars, that it was the sort of lawsuit that would ring the alarm in corporate boardrooms across America. And you'll meet his adversaries, foremost among them a crafty old trial lawyer, chairman of the litigation department at one of the biggest and most feared law firms in Boston." "The case turned into an epic struggle that took nine years of the lawyer's life. At the heart of the legal system, he was confronted by powerful and well-connected interests who would do anything to win. In the end, the struggle nearly cost him his sanity. He sacrified everything--home, friends, and reputation--not for money, but for what he believed to be the truth."--Jacket.
Keywords: Anderson, Anne, -- 1936?- -- Trials, litigation, etc. W.R. Grace & Co -- Trials, litigation, etc. Schlichtmann, Jan. Trials (Toxic torts) -- Massachusetts -- Boston. Groundwater -- Pollution -- Law and legislation -- Massachusetts -- Woburn. Drinking water -- Contamination -- Massachusetts -- Woburn. Liability for water pollution damages -- Massachusetts -- Woburn. Anderson, Anne, -- 1936?- W.R. Grace & Co. Drinking water -- Contamination. Groundwater -- Pollution -- Law and legislation. Liability for water pollution damages. Trials (Toxic torts) Massachusetts -- Boston. Massachusetts -- Woburn. Trinkwasserverschmutzung Wasserverschmutzung Zivilprozess Privaatrechtelijk milieurecht. Milieuverontreiniging. Aansprakelijkheid. Procesrecht. lawsuit. law -- pollution. drinking water -- contamination -- litigation. USA